Advertising : a cultural economy - McFall, Elizabeth Rose (Culture, representation, and identities., 2004)
With reference to cultural and economic life McFall argues that analysis has so far failed to engage with the production and consumption of adverts, and that a re-think of our understanding of advertising is long overdue. This text offers an understanding of the historical and material practices of the industry.